Body composition of English Premier League soccer players: Influence of playing position, international status, and ethnicity - Sutton, L.; Scott, M.; Wallace, J.; Reilly, T. (Journal of Sports Sciences, 2009)
Body composition is a key consideration in the physical make-up of professional soccer players. The aims of the present study were to determine whether the body composition of professional soccer players varied according to playing position, international status or ethnicity, and to establish which variables best distinguished the soccer players from a reference group. Body composition was assessed using dual-energy X-ray absorptiometry in 64 male professional soccer players. Measured variables included bone mineral density and the relative amounts of lean and fat mass. Data were analysed using analysis of variance and stepwise discriminant function. The soccer players recorded better values than a reference group (n = 24) for all body composition compartments. Percent lean mass and bone mineral density were the variables best able to identify the soccer players (95.5% correctly classified). Differences in body composition were evident between goalkeepers and outfield players, but not between outfield playing positions. No differences were found on the basis of international status. The non-Caucasian players demonstrated significantly lower percent body fat (9.2 ± 2.0%) than the Caucasian players (10.7 ± 1.8%). It was concluded that body composition is important for elite soccer players, but that homogeneity between players at top professional clubs results in little variation between individuals.